Legal Protection of Face and Voice as Copyrightable Objects in the Era of Deepfake Technology: A Comparative Analysis between Denmark and Indonesia from the Perspective of Ius Constituendum - Prihatin, Endang (Proceedings of International Conference of Graduate School on Sustainability, 2026)
The use of Artificial Intelligence (AI) to create hyper-realistic manipulations of images, videos, or audio recordings, and to alter visual and auditory content to produce synthetic media, has given rise to a new form of digital identity imitation that threatens privacy, personal dignity, and the integrity of public information. In response, Denmark has taken an innovative legal approach by proposing amendments to its copyright law that explicitly recognize an individual’s face and voice as protected elements under copyright. This article analyzes the legal mechanisms introduced by the Danish government regarding the copyright protection of facial and vocal identity and compares them with Indonesia’s Law Number 28 of 2014 on Copyright. The research employs a normative juridical method, emphasizing both a conceptual and a comparative approach to gain a broader perspective on the matter. The comparison of Indonesia’s and Denmark’s copyright laws reveals a significant legal gap. This disparity highlights the urgent need for Indonesia to follow Denmark’s example by revising its Copyright Law on the basis of the ius constituendum principle as a foundation for legal reform. Considering the challenges of the global digital era,